Establishment and Characterization of Stable Zein/Glycosylated Lactoferrin Nanoparticles to Enhance the Storage Stability and in vitro Bioaccessibility of 7,8-Dihydroxyflavone - Chen, Yufeng; Gao, Xiaojing; Liu, Shucheng; Cai, Qiuxing; Wu, Lijun; Sun, Yi; Xia, Guobin; Wang, Yueqi (Frontiers in Nutrition, 2022)
In this work, the lactoferrin (LF) was glycosylated by dextran (molecular weight 10, 40 and 70 kDa, LF 10K, LF 40K and LF 70K) via Maillard reaction as a stabilizer to establish zein/glycosylated LF nanoparticles and encapsulate 7,8-dihydroxyflavone (7,8-DHF). Three zein/glycosylated LF nanoparticles (79.27~87.24 nm) with low turbidity (<0.220) and PDI (<0.230) were successfully established by hydrophobic interactions and hydrogen bonding. Compared to zein/LF nanoparticles, zein/glycosylated LF nanoparticles furtherly increased stability to ionic strength (0~500 mM NaCl) at low pH conditions. Zein/glycosylated LF nanoparticles were nanoscale spherical shape and glycosylated LF changed surface morphology of zein nanoparticles. And encapsulated 7,8-DHF exhibited an amorphous state inside zein/glycosylated LF nanoparticles. Most importantly, zein/glycosylated LF nanoparticles had good water redispersibility, high encapsulation efficiency (above 98.50 %), favorable storage stability and bioaccessibility for 7,8-DHF, particularly LF 40K. Collectively, the above research provides a theoretical reference for the application of zein-based delivery systems.